IMPLEMENTASI MODEL MANAJEMEN BERBASIS SEKOLAH (MBS) PADA MADRASAH TSANAWIYAH SWASTA TPI TANJUNG PUTUS - Maulana Akbar Sanjani (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This research aims to find out how the implementation of school-based management model (MBS). The research was conducted at the Cape End TPI MTsS This study used a qualitative research. It is based on the consideration that this study revealed the implementation model of school-based management (SBM). Qualitative research is a research procedure that produces descriptive data in the form of words - words written or spoken of - people whose behavior can be understood. The subject of research directed to the search data from principals, vice-principals, teachers, and staff at the Cape End MTsS TPI. The data collection was obtained by observation, interview and document research. The findings of this study as follows: 1) the perception of the principal on MBS model application. 2) the pattern of school leadership in MBS. 3) application of management functions in the activities - activities pendidikan.4) MBS models in the improvement of education management.